MUSIK DALAM PENDIDIKAN ANAK USIA DINI - Rahman, Haryudi (EDUCHILD (Journal of Early Childhood Education), 2019)
This article reviews are about the outlook of comprehensive music education in early childhood. Music Education is discussed through several previous studies which is focusing their research on music education. Music as an expression of the way children express their feelings through singing a song with loud and soft dynamics. Music as communication of the way children convey messages through poetry when singing by moving. Music as a talent development on how to see the potential of the children through music. Music as creativity is how to children play musical instruments accompanied by movements in accordance with their imagination. Keywords: Music, Early childhood